Comparison of Gastro Retention Time and in vitro Release Profile studies of Ciprofloxacin HCl from Co-matrix Tablets of Hydrophilic Polymers - Islam, Muhammad Shahidul; Azam, Kazi Rashidul; Chowdury, Jakir Ahmed; Reza, Md Selim (Dhaka University Journal of Pharmaceutical Sciences, 2010)
Controlled release co-matrix tablets of Ciprofloxacin HCl were prepared with different types of bioadhesive polymers e.g. Methocel K4M, Methocel K 15M CR and Methocel K 100LV, Povidone K-30, and Xanthan gum. Tablets prepared by direct compression method were subjected to in-vitro drug dissolution study for 8 hours in a simulated gastric fluid media using USP dissolution apparatus II with 50 rpm at 37±0.5ºC. The bio-adhesive property was investigated in terms of retention time following in-vitro wash-off method. The concentrations of polymers were varied to investigate whether these variations can cause any change in release of Ciprofloxacin HCl molecule and bio-adhesion property or not. In most of the cases it is found that Methocel K4M and Methocel K100LV based co-matrix tablets release greater percentage of active drug than Methocel K15M CR based co-matrix tablets. Bio-adhesive strength of Methocel K15M CR and Xanthan gum based co-matrix tablets was proved to be maximum followed by Methocel K4M and Xanthan gum based co-matrices. Whereas Methocel K100LV and Xanthan gum based co-matrices showed little or poor muco-adhesion. Methocel K4M, K15M CR and Xanthan gum based formulations showed nearly zero-order release, on the other hand Methocel K100LV and Xanthan gum based formulation showed a burst release within one hour of dissolution. Finally it was revealed that Xanthan gum provided optimum bio-adhesion functioning as a synergist in co-matrices and comply the USP specification as a most suitable controlled release polymer. Key words: Gastro retention time; Direct Compression; Ciprofloxacin HCl; Methocel K4M; Methocel K15M CR; Methocel K100LV; Xanthan gum. DOI: 10.3329/dujps.v8i1.5338 Dhaka Univ. J. Pharm. Sci. 8(1): 67-73, 2009 (June)